ARTIFICIAL INTELLIGENCE FOR SUSTAINABLE AGRICULTURE IN UTTARAKHAND - Rahul Palaria; Shivam Pujari (International Educational Journal of Science and Engineering, 2025)
The integration of Artificial Intelligence (Al) into agriculture is revolutionizing farming practices in Uttarakhand, a Himalayan state with diverse agro-ecological zones and challenging topography. This chapter examines Al-driven interventions, including precision agriculture, crop yield forecasting, smart irrigation, disease prediction, and geospatial analytics tailored for hill farming. Leveraging machine learning (ML), deep learning (DL), Internet of Things (loT), and Geographic Information Systems (GIS), these technologies enable data-driven, resilient, and sustainable agriculture. We present Al architectures, cloud-based platforms, spatiotemporal analytics, and policy frameworks, supported by quantitative insights from Uttarakhand’s agricultural context.